2021
DOI: 10.4314/ahs.v21i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid lowering improves insulin sensitivity and lowers blood pressure: a meta-analysis of randomized parallel-controlled clinical trials

Abstract: Objectives: This meta-analysis aimed to investigate whether uric acid lowering treatment can improve β-cell function and insulin sensitivity. Methods: PubMed, Cochrane Library, EMBASE and China Biology Medicine were searched up to March 1, 2020. Rand- omized controlled clinical trials of urate lowering therapy in hyperuricemia patients were included in meta-analysis. Effect size was estimated as mean difference with 95% confidence interval (CI). Results: Our search yielded 7 eligible trials with 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…These improvements are indicative of a positive impact on a patient's long-term prognosis ( 34 ). Furthermore, a meta-analysis of seven eligible trials involving 503 participants with hyperuricemia demonstrated that urate-lowering therapy led to decreases in systolic and diastolic blood pressure, fasting insulin levels, and homeostasis model assessment of insulin resistance ( 35 ). However, it is worth noting that not all trials have shown consistent results, as some failed to provide sufficient evidence to support an effect on blood pressure, proteinuria, or other cardiovascular markers through urate-lowering therapy ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…These improvements are indicative of a positive impact on a patient's long-term prognosis ( 34 ). Furthermore, a meta-analysis of seven eligible trials involving 503 participants with hyperuricemia demonstrated that urate-lowering therapy led to decreases in systolic and diastolic blood pressure, fasting insulin levels, and homeostasis model assessment of insulin resistance ( 35 ). However, it is worth noting that not all trials have shown consistent results, as some failed to provide sufficient evidence to support an effect on blood pressure, proteinuria, or other cardiovascular markers through urate-lowering therapy ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these interventions did not yield a significant effect on HOMA-β and serum lipid levels. [28] There is a high degree of variability in the determination of HOMA-IR cutoff levels to define insulin resistance. The distribution of HOMA-IR varies according to the demographic characteristics of the subjects, such as age, sex, and race, making it difficult to estimate the optimal cutoff point.…”
Section: Discussionmentioning
confidence: 99%
“…However, these interventions did not yield a significant effect on HOMA-β and serum lipid levels. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%